2021
DOI: 10.3390/su131911053
|View full text |Cite
|
Sign up to set email alerts
|

A Classification Analysis of the High and Low Levels of Global Competence of Secondary Students: Insights from 25 Countries/Regions

Abstract: The reinforcement of global competence is vital for students to thrive in a rapidly changing world. This study explores the synergistic effects of both student and school factors on the classification of secondary students with high and low levels of global competence. Data are selected based on 208,556 secondary students from 6902 schools in 25 countries/regions and extracted from the Programme for International Student Assessment (PISA) 2018 datasets. Different from previous research, in this study, data sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
(72 reference statements)
0
8
1
Order By: Relevance
“…It is important to note the contrast with findings by Hu & Hu (2021), who reported minimal impact of combined learning strategies in a different educational context. This underscores the importance of considering contextual factors such as classroom environment, student demographics, and subject matter when applying integrated learning models.…”
Section: Discussioncontrasting
confidence: 81%
“…It is important to note the contrast with findings by Hu & Hu (2021), who reported minimal impact of combined learning strategies in a different educational context. This underscores the importance of considering contextual factors such as classroom environment, student demographics, and subject matter when applying integrated learning models.…”
Section: Discussioncontrasting
confidence: 81%
“…Kang et.al. [12] and Hu and Hu [13] in their study argue that exposure to mass media, migration and contact with foreigners on daily basis could transform individuals' understanding of foreign cultures and attitudes towards certain global issues. Certain problems, as Hu and Hu argue, may not have reached the consensus in regard to their solution, which is why related approaches, policies and experiences of different nations may contribute to a greater familiarity among students, and as a result, cultivate their global competence [13].…”
Section: Factors Affecting Students' Global Competencementioning
confidence: 99%
“…[12] and Hu and Hu [13] in their study argue that exposure to mass media, migration and contact with foreigners on daily basis could transform individuals' understanding of foreign cultures and attitudes towards certain global issues. Certain problems, as Hu and Hu argue, may not have reached the consensus in regard to their solution, which is why related approaches, policies and experiences of different nations may contribute to a greater familiarity among students, and as a result, cultivate their global competence [13]. Meanwhile, analysis of students from apparel programs at US and Korean universities, who participated in a series of fashion-related cross/intercultural projects, show that global mass media has exerted the strongest influence on students' global competence acquisition.…”
Section: Factors Affecting Students' Global Competencementioning
confidence: 99%
See 1 more Smart Citation
“…First, learning emotion affects learning cognition. In a study of learners' online participation in learning tasks, researchers found that learning emotion affects learning cognitive style (Hu & Hu, 2021). Second, learning emotion affects learning effectiveness.…”
Section: Research Status Of Students' Learning Emotions In Informatio...mentioning
confidence: 99%